The Impact of The Amount of The South Sulawesi Koni Grant Budget on The XXI PON Aceh-Sumut 2024 - Syafir, Muhammad Isnawan; Saleh, M. Sahib; Saleh , Muh. Syahrul; Muslim, Muslim; Gorap, Stefanie Inggried (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
A This study aims to analyze the impact of grant funding allocations on the performance of athletes from South Sulawesi in preparation for the 2024 National Sports Week (PON XXI) in Aceh–North Sumatra. The research employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation from various online news sources, including KONI South Sulawesi. The findings reveal that although a total grant of IDR 31.5 billion was allocated for PON XXI—IDR 17.5 billion for KONI South Sulawesi and IDR 14 billion for the South Sulawesi Youth and Sports Office (Dispora)—athlete performance declined, with South Sulawesi ranking 16th out of 39 provinces. In contrast, during PON XIX in West Java in 2016, a budget of IDR 80 billion resulted in 12 gold medals and a 12th-place finish out of 34 provinces. At PON XX in Papua in 2021, with a budget of IDR 30 billion, South Sulawesi earned 11 gold medals and ranked 11th out of 34 provinces. Several factors were found to affect the effectiveness of grant utilization, including delayed fund disbursement, lack of transparency, and insufficient strategic planning in athlete development and training program implementation. Moreover, weak coordination among local government, KONI, and sports federations led to inefficiencies in the distribution and use of funds. The study concludes that the amount of grant funding does not necessarily correlate with improved athletic performance unless supported by an effective, transparent, and accountable management system.